Teacher Inquiry into Student Learning: - The TISL Heart Model and Method for use in Teachers' Professional Development - Cecilie J. Hansen; Barbara Wasson (Universitetsforlaget, 2016)
Researchers have recently been calling for new models of teacher education and professional development for the 21st century. Teacher inquiry, where the teacher's own practice is under investigation, can be seen both as a way to improve day-to-day teaching in the classroom and as professional development for teachers. As such, it should also have a role in teacher education. In this article, we present the iterative development of the TISL Heart, a theory-practice model and method of teacher inquiry into student learning, which has a particular emphasis on the use of student results generated in the information and technology-rich classroom. This article proposes that this practice-near model is particularly relevant for teacher education, as it draws upon existing practices in using student data at a progressive school that focuses on the use of technology to enhance student learning. The article concludes by discussing the implications for its role in teacher education, particularly related to data literacy and its use in teaching.